Invisible rulers : the people who turn lies into reality - DiResta, Renée autor (PublicAffairs, 2024)
By revealing the machinery and dynamics of the interplay between influencers, algorithms, and online crowds, DiResta illustrates the way propagandists deliberately undermine belief in the fundamental legitimacy of institutions that make society work. These invisible rulers create bespoke realities to revolutionize politics, culture, and society. Their work is driven by a simple maxim: if you make it trend, you make it true. DiResta predicts the consequences and offers ways for leaders to adapt and fight back.